Pemanfaatan media kartu edukatif adventure path sebagai inovasi pembelajaran sejarah manusia purba di SD Negeri Krikilan 1 - Iswanti Iswanti; Isnaeni Hasna Hanisah; Annisa Rahmawati; Genta Pandu Wicaksana Naufal Ristofandi; Anna Arbangatun Sholikah (Penamas: Journal of Community Service, 2026)
History education in elementary schools is often considered boring and difficult for students to understand due to its abstract presentation and the dominance of lecture and memorisation methods. This condition results in low interest in learning and limited understanding of historical context among students. This community service program aims to improve understanding of ancient human history through an innovative medium in the form of Adventure Path cards. The activity was carried out at Krikilan 1 Public Elementary School, involving 70 students in grades IV–VI. The Adventure Path media consists of two types, namely Travel Cards and Quiz Cards. The Travel Cards contain material on the evolution of early humans in Indonesia and the stages of early life, while the Quiz Cards contain interactive questions to reinforce understanding through discussion. The implementation results showed a significant increase in student involvement in the classroom, as evidenced by students being more active, enthusiastic, and able to explain the sequence of evolution and the stages of ancient human life coherently. The joyful learning approach made history learning more enjoyable and meaningful, and contributed to efforts to preserve cultural values from an early age.